The Effect Of Acupressure On Decreasing The Frequency Of Emesis Gravidarum Pregnant Women In Trimester I - Ika Nur Saputri (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Embissive Gravidarum usually occurs in pregnant trimester i-ups that reaches 12.5% of all the amount of pregnancy in the world. Complementary therapy to reduce nausea vomites in pregnant women with acupressure at P6 point. Acupressure can overcome pain, assist stress management and improve relaxation. The purpose of this study is to know the effect of acupressure therapy toward the decrease of frequency of gravidarum emesis in pregnant trimester i. This study uses quantitative method with experimental quasi design and is done at the Siswani Lubuk Pakam midwife clinic. The population used is all pregnant women trimester I have embissive gravidarum with the number of samples of 18 people with details 9 people given intervention and 9 people as control. The results showed that there was a decrease in the frequency of embissive gravidarum (P-value 0.317> 0.05) in the intervention group and control group there was no decline. Conclusion There is an influence of the acupressure on the decrease of frequency of gravidarum emesis in pregnant women trimester I.